A beautiful noise [invention of STM and AFM]. - Goldstein, H. (IEEE spectrum)
The author talks to Gerd Binnig from IBM's Zurich Research Laboratory about he invented the scanning tunneling microscope (STM) and atomic force microscopy (AFM) which launched the nanotech revolution.